Planteamientos críticos y alternativos en Geografía - Pozo, Paz Benito del (2004)
This paper is a product of the reflection on geographic thought carried out in the defence of the author’s teaching material at the University of León, Spain. Reviewed and adapted for publication, this summarised version analyses the contribution of so-called radical or critical geographies to the construction of current human geography, as well as other influential approaches derived from the limitations and the wearing-down of radical discourse, paying special attention to humanistic geography. Lastly, some alternative approaches, increasingly important within the framework of a progressively more plural geography around which new disciplinary horizons revolve, are sketched out.